Romper as fronteiras: conexões entre anarquistas na Rússia e no Japão - Uehara, Luíza (Ecopolítica, 2018)
Mikhail Bakunin, anarquista nascido na Rússia, conseguiu fugir do exílio da Sibéria inaugurando uma rota que passava pelo Japão para chegar aos Estados Unidos ou Europa. Essa È uma das procedências das relações entre anarquistas russos e anarquistas japoneses, fortalecida com as obras de Lev Metchnikoff - amigo de Bakunin - e no decurso da Guerra Russo-Japonesa. Anos depois o anarquista Ôsugi Sakae, responsável pela tradução de obras de Bakunin para o japonês foi crítico à Revolução de 1917 e rompeu com o bolchevismo que tentava tomar a direção editorial de suas publicações. Apresenta-se brevemente nesse artigo algumas dessas conexões entre anarquistas no Japão e na Rússia para traÁar recordações no presente daqueles que não temeram enfrentar o governo do Imperador, da nação, do sindicato, e/ou do partido. Palavras-chave: anarquismos no Japão, Era Meiji, Ôsugi Sakae, Revolução Russa. ABSTRACT: Mikhail Bakunin was a Russian-born anarchist who inaugurated a route through Japan to get to United States and Europe, while scaping from Siberia’s exile. During the few days he spent in Japan he did little contact with the people, but could observe its early modernization in the western standards. This is one of the begginings of the relationships between Russian and Japanese anarchists. Which was strengthened by the work of a close Bakuninís friend, Lev Metchnikoff, specially, during the Russian-Japanese war. Later on, the anarchist Ôsugi Sakae, who translated Bakunin’s work to Japanese language, became a critic to the 1917’s Russian Revolution, and split with the bolcheviks who were trying to take the editorial direction of his publications. This article shows briefly some of these connections between anarchists in Russia and Japan bringing to the present the memories of those who didn’t fear the Imperor, nation, union and/or the party government. Keywords: anarchism in Japan, Meiji period, Ôsugi Sakae, Russian Revolution.